Socioeconomic differences in health-care use and outcomes for stroke and ischaemic heart disease in China during 2009-16: a prospective cohort study of 0·5 million adults - Muriel Levy, MSc; Yiping Chen, DPhil; Robert Clarke, ProfFRCP; Derrick Bennett, PhD; Yunlong Tan, MSc; Yu Guo, MSc; Zheng Bian, MSc; Jun Lv, PhD; Canqing Yu, PhD; Liming Li, ProfMPH; Winnie Yip, ProfPhD; Zhengming Chen, ProfDPhil; et al. (Elsevier, 2020)
Summary: Background: China initiated major health-care reforms in 2009 aiming to provide universal health care for all by 2020. However, little is known about trends in health-care use and health outcomes across different socioeconomic groups in the past decade. Methods: We used data from the China Kadoorie Biobank (CKB), a nationwide prospective cohort study of adults aged 30-79 years in 2004-08, in ten regions (five urban, five rural) in China. Individuals who were alive in 2009 were included in the present study. Data for all admissions were obtained by linkage to electronic hospital records from the health insurance system, and to region-specific disease and death registers. Generalised linear models were used to estimate trends in annual hospital admission rates, 28-day case fatality rates, and mean length of stay for stroke, ischaemic heart disease, and any cause in all relevant individuals. Findings: 512 715 participants were recruited to the CKB between June 25, 2004, and July 15, 2008, 505 995 of whom were still alive on Jan 1, 2009, and contributed to the present study. Among them, we recorded 794 824 hospital admissions (74 313 for stroke, 69 446 for ischaemic heart disease) between 2009 and 2016. After adjustment for demographic, socioeconomic, lifestyle, and morbidity factors, hospitalisation rates increased annually by 3·6% for stroke, 5·4% for ischaemic heart disease, and 4·2% for any cause, between 2009 and 2016. Higher socioeconomic groups had higher hospitalisation rates, but the annual proportional increases were higher in those with lower education or income levels, those enrolled in the urban or rural resident health insurance scheme, and for those in rural areas. Lower socioeconomic groups had higher case fatality rates for stroke and ischaemic heart disease, but greater reductions in case fatality rates than higher socioeconomic groups. By contrast, mean length of stay decreased by around 2% annually for stroke, ischaemic heart disease, and any cause, but decreased to a greater extent in higher than lower socioeconomic groups for stroke and ischaemic heart disease. Interpretation: Between 2009 and 2016, lower socioeconomic groups in China had greater increases in hospital admission rates and greater reductions in case fatality rates for stroke and ischaemic heart disease. Additional strategies are needed to further reduce socioeconomic differences in health-care use and disease outcomes. Funding: Wellcome Trust, Medical Research Council, British Heart Foundation, Cancer Research UK, Kadoorie Charitable Foundation, China Ministry of Science and Technology, and Chinese National Natural Science Foundation.